Microbial Pattern of Neonatal Sepsis in the Neonatal Intensive Care Unit of dr. Ramelan Navy Central Hospital - Stefani Miranda; Aminuddin Harahap; Dominicus Husada; Fara Nayo Faramarisa (Hindawi Limited, 2024)
Background. The morbidity and mortality rates from neonatal sepsis remain high. However, there is limited information about the microbial pattern of neonatal sepsis in Indonesia. Microbial patterns can give an overview of the hygiene of an environment and act as a determinant for choosing definitive antibiotic treatment in neonatal sepsis patients. The organisms that cause neonatal sepsis differ from unit to unit and from time to time within the same unit. Objectives. This study is aimed at discovering the microbial pattern of neonatal sepsis in the Neonatal Intensive Care Unit (NICU), dr. Ramelan Navy Central Hospital, in 2021-2022. Methods. This is a retrospective, cross-sectional study that takes secondary data from the NICU and clinical microbiology department of dr. Ramelan Navy Central Hospital. Data that met the inclusion and exclusion criteria available between January 1, 2021, and December 31, 2022, were collected. Patients whose blood cultures were positive for bacterial growth and diagnosed with sepsis were selected as the study sample. Results. Out of 174 samples, 93 (53.4%) were found positive for bacterial infection and diagnosed as neonatal sepsis. Gram-negative isolates (96.8%) were predominant. Sixty-point-two percent of Klebsiella pneumoniae XDR, 19.4% of Klebsiella pneumoniae ESBL, and 8.6% of Burkholderia cepacia XDR were identified. The gram-positive isolates found in this study were only 3 samples (3.2%). Two-point-one percent of MRSA and 1.1% of Staphylococcus haemolyticus MDR were identified. Conclusion. The most common microorganisms causing neonatal sepsis in our NICU were gram-negative bacteria, particularly Klebsiella pneumoniae XDR. Following the recommended infection control procedures, practicing good hand hygiene, and having access to basic supplies and equipment are important to prevent and reduce the incidence of sepsis.